Selective protection of human cardiomyocytes from anthracycline cardiotoxicity by small molecule inhibitors of MAP4K4 - Schneider,M; Golforoush,P; Narasimhan,P; Chaves-Guerrero,P; Lawrence,E; Newton,G; Yan,R; Harding,S; Perrior,T; Chapman,K (Scientific Reports, 2020)
Given the poor track record to date of animal models for creating cardioprotective drugs, human pluripotent stem cell-derived cardiomyocytes (hPSC-CMs) have been proposed as a therapeutically relevant human platform to guide target validation and cardiac drug development. Mitogen-Activated Protein Kinase Kinase Kinase Kinase-4 (MAP4K4) is an “upstream” member of the MAPK superfamily that is implicated in human cardiac muscle cell death from oxidative stress, based on gene silencing and pharmacological inhibition in hPSC-CMs. A further role for MAP4K4 was proposed in heart muscle cell death triggered by cardiotoxic anti-cancer drugs, given its reported activation in failing human hearts with doxorubicin (DOX) cardiomyopathy, and its activation acutely by DOX in cultured cardiomyocytes. Here, we report successful protection from DOX in two independent hPSC-CM lines, using two potent, highly selective MAP4K4 inhibitors. The MAP4K4 inhibitors enhanced viability and reduced apoptosis at otherwise lethal concentrations of DOX, and preserved cardiomyocyte function, as measured by spontaneous calcium transients, at sub-maximal ones. Notably, in contrast, no intereference was seen in tumor cell killing, caspase activation, or mitochondrial membrane dissipation by DOX, in human cancer cell lines. Thus, MAP4K4 is a plausible, tractable, selective therapeutic target in DOX-induced human heart muscle cell death.